Projected Mushroom Type Phase‐Change Memory - Ghazi Sarwat, Syed; Philip, Timothy M.; Chen, Ching‐Tzu; Kersting, Benedikt; Bruce, Robert L.; Cheng, Cheng‐Wei; Li, Ning; Saulnier, Nicole; BrightSky, Matthew; Sebastian, Abu (Advanced functional materials, 2021)
Phase‐change memory devices have found applications in in‐memory computing where the physical attributes of these devices are exploited to compute in places without the need to shuttle data between memory and processing units. However, nonidealities such as temporal variations in the electrical resistance have a detrimental impact on the achievable computational precision. To address this, a promising approach is projecting the phase configuration of phase change material onto some stable element within the device. Here, the projection mechanism in a prominent phase‐change memory device architecture, namely mushroom‐type phase‐change memory, is investigated. Using nanoscale projected Ge2Sb2Te5 devices, the key attributes of state‐dependent resistance, drift coefficients, and phase configurations are studied, and using them how these devices fundamentally work is understood. Nonvolatile memory devices, which can both store and compute information are emerging building blocks for brain‐inspired and in‐memory computing. Here, the nuts and bolts of a “projected” mushroom type phase change computational device that can decouple the device's readout characteristics from the noisy properties of the phase change material are discussed.